2010
DOI: 10.1111/j.1476-5381.2010.00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms mediating the ability of caffeine to influence MDMA (‘Ecstasy’)‐induced hyperthermia in rats

Abstract: Background and purpose: Caffeine exacerbates the hyperthermia associated with an acute exposure to 3,4 methylenedioxymethamphetamine (MDMA, 'Ecstasy') in rats. The present study investigated the mechanisms mediating this interaction. Experimental approach: Adult male Sprague-Dawley rats were treated with caffeine (10 mg·kg ) exacerbated MDMA-induced hyperthermia. Conclusions and implications:A mechanism comprising 5-HT and catecholamines is proposed to mediate MDMA-induced hyperthermia. A combination of adenos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 70 publications
2
40
0
Order By: Relevance
“…Chaperon et al (2003) reported that dopamine D 1 and D 2 receptor may be involved in a co-operative manner to regulate core body temperature in rats where both SCH 23390 and the selective dopamine D 2 receptor antagonist L-741,626 were found to reverse hypothermia induced by the dopamine D 2 and D 3 receptor agonists trihydroxy-N-n-propylnoraporphine (TNPA) or PD 128907. Overall, the results are consistent with previous results from our laboratory in support of a dopamine-related mechanism that may account for a caffeine-induced switch from MDMA-induced hypo-to hyperthermia (Vanattou-Saïfoudine et al 2010).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Chaperon et al (2003) reported that dopamine D 1 and D 2 receptor may be involved in a co-operative manner to regulate core body temperature in rats where both SCH 23390 and the selective dopamine D 2 receptor antagonist L-741,626 were found to reverse hypothermia induced by the dopamine D 2 and D 3 receptor agonists trihydroxy-N-n-propylnoraporphine (TNPA) or PD 128907. Overall, the results are consistent with previous results from our laboratory in support of a dopamine-related mechanism that may account for a caffeine-induced switch from MDMA-induced hypo-to hyperthermia (Vanattou-Saïfoudine et al 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Doses of caffeine and MDMA were chosen from previous reports of the interaction between caffeine and MDMA in rats (McNamara et al 2006(McNamara et al , 2007. The selective dopamine D 1/5 antagonist, SCH 23390, was used in this study at a dose of 1 mg/kg which blocks MDMA-induced hyperthermia and its exacerbation by caffeine in group-housed rats (Vanattou-Saïfoudine et al 2010). The selective dopamine D 2 receptor antagonist sulpiride was used in this study at a dose of 100 mg/kg.…”
Section: Drug Preparation and Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The core body temperature was assessed rectally by a digital probe thermometer (Omron, Kyoto, Japan) following the method previously described (40). The spontaneous physical activity was recorded for 1 h in locomotion cages (45 cm × 45 cm) by using AniLab Software (AniLab Software & instruments, Ningbo, China) following the manufacturer's instructions.…”
Section: Core Temperature and Spontaneous Physical Activitymentioning
confidence: 99%
“…Adenosine A 1 receptors have a widespread distribution in the brain, with highest levels in the hippocampus, cerebral cortex, hypothalamus and cerebellum, and low levels in the basal ganglia, while A 2A receptors are found mainly in dopamine rich brain regions such as the striatum and nucleus accumbens. It is the effect of caffeine on dopamine release that is commonly attributed to the toxic effects (hyperthermia, cardiovascular toxicity and seizure threshold) of its coadministration with MDMA (Vanattou-Saifoudine et al, 2010b;Vanattou-Saifoudine et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%